Unix survival guide - Stein, Lincoln D (Current protocols in bioinformatics, 2007)
For a mixture of historical and practical reasons, much of the bioinformatics software discussed in this series runs on Linux, Mac OSX, Solaris, or one of the many other Unix variants. This appendix provides the novice with easy-to-understand information needed to survive in the Unix environment.